REHABILITATION TREATMENT OF LUMBARIZATION-RELATED PATHOLOGIES VIA MANUAL THERAPY (World Science, 2020)
Lumbarization is one of the most common congenital anomalies of the lumbosacral spine in which the first segment of the sacrum does not merge with the second segment and becomes part of the lumbar vertebrae, the sixth transitional segment is present in the lumbar region and the sacral region, whose vertebrae fuse together, consists of only four segments. The lumbosacral spine has a significant role in the human body, it not only protects the spinal cord and spinal nerves, but also maintains and transfers body weight to the lower extremities and plays an important part in posture and movement. Therefore, lumbarization disrupts normal functioning of the spine and creates a risk of pathological changes in the human body.Lumbarization often leads to certain clinical symptoms that can restrict the patient's movement and cause pain not limited to the spine only. Usually, patients with lumbarization may experience pain during movement. This may cause great difficulty in performing daily activities. As a congenital anatomic anomaly, lumbarization currently has no permanent cure, but pathologies associated with it can be successfully managed with manual therapy.